2017
DOI: 10.1177/0954008317729741
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and thermal degradation kinetics of thermoplastic polyimide based on BAPP

Abstract: Two kinds of thermoplastic polyimides (PIs) were synthesized via a two-step method with 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP), 4,4′-oxydianiline (ODA) diamine, and 3,3′,4,4′-benzophenonetetracarboxylic dianhydride (BTDA), and their thermal degradation kinetics was studied by thermogravimetric analysis at different heating rates under nitrogen. Derivative thermogravimetric analysis curves indicated a simple, single-stage degradation process in PI BTDA-BAPP and a two-stage degradation process in PI BTD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…DuPont has obtained a commercial thermoplastic PI film, Kapton ® -KJ, by introducing a large number of flexible ether linkages, but its glass transition temperature (T g ) is only 220°C [16]. The films derived from 3,3′,4,4′-benzophenonetetracarboxylic dianhydride (BTDA) and flexible diamines, such as 2,2-bis [4-(4- [18]. It has also been found that BTDA/TPE-R is a new type of high temperature semi-crystalline PI [15].…”
Section: Introductionmentioning
confidence: 99%
“…DuPont has obtained a commercial thermoplastic PI film, Kapton ® -KJ, by introducing a large number of flexible ether linkages, but its glass transition temperature (T g ) is only 220°C [16]. The films derived from 3,3′,4,4′-benzophenonetetracarboxylic dianhydride (BTDA) and flexible diamines, such as 2,2-bis [4-(4- [18]. It has also been found that BTDA/TPE-R is a new type of high temperature semi-crystalline PI [15].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of F-or S-rich structural motifs determines other, usually toxic volatiles. The decomposition process follows several pathways: depolymerization, pyrolytic reformation, successive homolytic and hydrolytic cleavages, hydrogen ablation, progressive molecular rearrangements, and loss of organic functionality through radical scission [140,145,146]. In every pathway, CO2 remains the main degradation product, while the nature of the other volatiles is dictated by the chemical structure of the polymer.…”
Section: Thermal (Oxidative) Degradationmentioning
confidence: 99%
“…It is an important parameter to evaluate the thermal stability of polymers. 26 The higher the E a , the better the thermal stability of the polymer. According to the relevant thermodynamic values obtained from the TG and DTG curves of two kinds of polyimide films at different heating rates, the E a s of two kinds of PIs in different atmospheres were calculated by Flynn-Wall-Ozawa, Kissinger-Akahira-Sunose and Kissinger methods, respectively, and the values were summarized and compared in Table 4.…”
Section: Determination Of E a Smentioning
confidence: 99%